2022
DOI: 10.1177/23312165221134003
|View full text |Cite
|
Sign up to set email alerts
|

Baseline pupil size encodes task-related information and modulates the task-evoked response in a speech-in-noise task

Abstract: Pupillometry data are commonly reported relative to a baseline value recorded in a controlled pre-task condition. In this study, the influence of the experimental design and the preparatory processing related to task difficulty on the baseline pupil size was investigated during a speech intelligibility in noise paradigm. Furthermore, the relationship between the baseline pupil size and the temporal dynamics of the pupil response was assessed. The analysis revealed strong effects of block presentation order, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(272 reference statements)
1
5
0
Order By: Relevance
“…Listeners develop expectations about upcoming listening challenges based on their knowledge of the probabilistic properties of English , the ease of listening to familiar voices (Papesh, Goldinger, & Hout, 2012), cues about upcoming acoustic conditions (e.g., noise that is informative of an upcoming SNR; Seropian et al, 2022), and experience with hearing loss that leads them to expect difficulty in most conversations (Ayasse & Wingfield, 2020). Furthermore, aligned with previous results (Knapen et al, 2016;Relaño-Iborra et al, 2022), baseline pupil size was observed to affect the shape (not just the height) of the pupil response across time. Thus, performing baseline correction on the TEPR without first examining the impact of the listening condition of interest on the pre-stimulus pupil size has the potential to minimize, eliminate, or potentially artifactually reverse expected effects of listening demands on the TEPR.…”
Section: Implications For Theories and Analyses Of Listening Effortsupporting
confidence: 82%
See 3 more Smart Citations
“…Listeners develop expectations about upcoming listening challenges based on their knowledge of the probabilistic properties of English , the ease of listening to familiar voices (Papesh, Goldinger, & Hout, 2012), cues about upcoming acoustic conditions (e.g., noise that is informative of an upcoming SNR; Seropian et al, 2022), and experience with hearing loss that leads them to expect difficulty in most conversations (Ayasse & Wingfield, 2020). Furthermore, aligned with previous results (Knapen et al, 2016;Relaño-Iborra et al, 2022), baseline pupil size was observed to affect the shape (not just the height) of the pupil response across time. Thus, performing baseline correction on the TEPR without first examining the impact of the listening condition of interest on the pre-stimulus pupil size has the potential to minimize, eliminate, or potentially artifactually reverse expected effects of listening demands on the TEPR.…”
Section: Implications For Theories and Analyses Of Listening Effortsupporting
confidence: 82%
“…The present study examines the relationship between attention mobilization-how individuals prepare their attention in anticipation of an upcoming task-and listening effort allocation-how listeners deploy and use their attentional resources during the task-when listeners can anticipate the difficulty of the upcoming trial. Extending the results of Relaño-Iborra et al (2022), the present study focuses on trial-level variation in attention mobilization for a sustained listening task involving exact stimulus repetitions. Participants listened to three presentations of several 60-s long audiobook passages and were instructed to attend to one of two competing speakers in an easy or difficult listening situation, determined by SNR.…”
Section: Goals Of the Present Studymentioning
confidence: 98%
See 2 more Smart Citations
“…During active tasks (i.e., those that elicit behavioral responses to stimuli), the magnitude of the task-evoked pupil response (TEPR) would be expected to be maximal at moderate levels of LC activity, given the nonmonotonic (inverted-U shaped) relationship between LC phasic and tonic activity (Aston-Jones & Cohen, 2005). Phasic peak pupil dilation following VNS onset may likewise be expected to vary as a function of prestimulus baseline pupil size (Johns et al, in press; Relaño-Iborra et al, 2022), which reflects tonic LC activity (Mridha et al, 2021). However, a monotonic relationship between pupil dilation and LC activity might be expected for passive tasks, given evidence from mice that shows pupil dilation to increase monotonically with LC spiking rate (Megemont et al, 2022) as well as iVNS intensity, pulse width, and stimulation rate (Mridha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%